Evaluation of carbon vapour deposition technique for whiskerization treatment of carbon fibers - Abdul Rashid, Suraya; Vargis, C.; Yunus, Robiah; Shamsudin, Shuhaimi (Federation of Engineering Institutions of Islamic Countries, 2006)
The main objective of this work was to evaluate the effectiveness of the chemical vapour deposition (CVD) technique for the whiskerization treatment of polyacrylonitrile (PAN) based carbon fibers. Carbon whiskers were produced by a benzene-ferrocene gas reaction inside a high temperature tube furnace. The work focuses on one pre-treatment study and two treatment studies, which were (i) the pre-treatment effect of heating rate on the carbon fibers, (ii) the morphology of treated carbon fiber samples at three different regions inside the furnace, and (iii) the effect of different hydrogen flow rates on the treatment process. The reaction temperature and duration was set at 900oC and 30 minutes respectively. Treated samples were analysed using scanning electron microscopy (SEM). The pre-treatment study indicated that a heating rate of 5oC/min caused the least amount of damage to the carbon fibers. The treatment studies showed that whiskers were successfully grown onto the carbon fibres with the highest amount of whiskerization occurring for samples nearest the inlet region of the furnace. Different whisker structures were also observed at different hydrogen flow rates.